Carvacrol loaded nanostructured lipid carriers as a promising parenteral formulation for leishmaniasis treatment - Galvão, Juliana G. (2020)
Universidade Federal de Sergipe. Departamento de Farmácia. São Cristóvão, SE, Brasil.